Surgical treatment of isolated coarctation of the aorta: 18 years' experience. - Behl, P R (1987)
From March 1967 to February 1985 91 patients aged from 11 months to 53 years underwent surgical treatment of isolated coarctation of the aorta. The surgical procedures in descending order of frequency, were: resection with end to end anastomosis, resection with replacement by a tube graft, patch aortoplasty, and bypass graft. Resection with end to end anastomosis was achieved mainly in younger patients. The number of patients needing other procedures increased with advancing age. Eighty six patients have been followed up (mean 10 years). There were no hospital or late deaths and none of the patients suffered from spinal cord injury. There were three recurrences of the coarctation, all in patients who had had primary reconstruction below the age of one year. The patients were divided into three groups by age: group 1, 0-5 years; group 2, 6-15 years; and group 3, over 15 years. It was found that there was no late hypertension in group 1 while hypertension persisted in 7% of group 2 and in 28% of group 3. Fifty per cent of the patients with persistent hypertension were above the age of 20 years at the time of operation and had resection with replacement by a tube graft. It is recommended that elective surgery for coarctation of the aorta should be performed at the age of 3-5 years to avoid both recurrence of stenosis and persistent hypertension.